Analysis of difficulties learning accounting for Students Private High School St. Darius Larantuka - Beribe, Maria Fatima (Universitas Pahlawan Tuanku Tambusai, 2025)
This study adopts a descriptive approach with a qualitative methodology, aiming to identify the factors contributing to learning difficulties in Accounting, specifically regarding the Worksheet subtopic, among students in the XII SOS class at St. Darius Larantuka Private High School for the academic year 2024-2025. The research employs a target area site method, with the selection of research subjects determined through a snowball sampling technique. Data collection is conducted through interviews, observations, and documentation, which are subsequently analyzed in three stages: data reduction, presentation, and conclusion drawing. The findings indicate that students' difficulties in learning Accounting related to Worksheets stem from a lack of foundational knowledge and skills in accounting, such as the ability to analyze, calculate, and record transaction data; a low interest in learning accounting; less engaging teaching methods; and limited resources for accounting education, including the availability of textbooks and other supporting materials.